Evaluasi Program Tahfizh Qur’an di SD Negeri 10 Lubuk Layang Kecamatan Rao Selatan Kabupaten Pasaman - Vivi Moniza (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2026)
This research aims to: 1) evaluate the context of the Qur’an recitation program for the SD Negeri 10 Lubuk Layang. 2) evaluate the input of the Qur’an recitation program for the SD Negeri 10 Lubuk Layang. 3) evaluate the process of the Qur’an recitation program for the SD Negeri 10 Lubuk Layang. 4) evaluate the product of the Qur’an recitation program for the SD Negeri 10 Lubuk Layang. This research is an evaluative type of research with a descriptive qualitative approach, in this study using the evaluation model of the Stufflebeam theory, namely CIPP (Context, Input, Process, Product). Data obtained by interview, observation and documentation. Data analysis used in this study by reducing data, after that it is presented in the form of description and verified by drawing conclusions.The results of this study indicate that: 1) the evaluation results of of the Qur’an recitation program for the SD Negeri 10 Lubuk Layang show that the program has clear goals and plans. 2) the results of evaluating the input of the Qur’an tahfizh program are known that the competence of the thafizh teacher is appropriate because it has memorization and the ability to understand the reading of the al-Qur’an, while students participating in the tahfizh program have high memorization in memorizing.Besides this program is supported by good infrastructure, especially with the guidance book that is owned by each student. 3) the results of the evaluation of the Qur’an tahfizh program shows that the process of implementing the qur’an tahfizh runs efficiently and in accordance with what hasbeen agrred upon. The method used is talaqqi, and which is an obstacle in the implementation of tahfizh Qur’an namely the lack of time tahfizh hours and the lack of tutors of tahfizh Qur’an. 4)Product evaluation results show that the achievement of the target memorization of students goes according to the target, althought there are still those who have not passed the test but iit can be overcome by the teacher tahfizh. The conclusion is that the Qur’an tahfizh program in SD Negeri 10 Lubuk Layang runs according to a predetermined plan, although in its implementation there are some obstacles that must be corrected. Tahfizh achievementsof good students are caused by the existence of good cooperation between schools and parents at home to jointly provide encouragement, support and supervision in memorizing children’s Qur’an